CHARACTERISTICS RELATIONSHIP OF WORKERS AND INTENSITY OF WORK ENVIRONMENT NOISE WITH TINNITUS COMPLAINTS IN GAS INDUSTRIAL WORKERS IN SIDOARJO - Dwi Sunarto; Ririh Yudhastuti (Universitas Airlangga, 2022)
Introduction: Industrial progress is characterized by the increasing use of machinery in factory which has a negative impact on workers' health, one of which is tinnitus symptoms. Tinnitus is a hearing loss due to exposure to noise. The purpose of this study was to determine the relationship of worker characteristics and intensity of work environment noise with tinnitus symptoms in gas industry workers in Sidoarjo. Methods: Based on the study design, this study used analytic research, in terms of time including cross-sectional research. Research variables include age, years of service, noise intensity and tinnitus symptoms. Data are from observation, measurement, questionnaire filling and interview. Result: The results showed that there was a relationship between noise intensity and tinnitus symptoms (p = 0.033). There was no relationship between the age of workers and tinnitus symptoms (p = 1.000). There was no significant relationship between years of work (p = 0.505) with tinnitus symptoms suffered by workers at PT. X Sidoarjo Gas Industry. There was no association between exposure pattern and complaints of tinnitus (p=0.165). Conclusion: So as to reduce the risk of tinnitus complaints the company can apply the use of ear protector for workers and install silencers that can absorb sound with high noise intensity such as glasswool, rockwool, foam, cellulose fiber and acourete fiber carpets to reduce noise.